Investigating Aerodynamic Characteristics of a Fixed-Wing Hybrid UAV During Hover-Forward Transition Flight Phase - Aqeel, Muhammad Munib Abid; Zulkafli, Mohd Fadhli; Pairan, Mohammad Fahmi (Progress in Aerospace and Aviation Technology, 2024)
In the past few years, unmanned aerial vehicles (UAVs) have been employed extensively in agricultural observation, wildlife protection, and traffic monitoring sectors. Hybrid UAVs combine the advantages of both multirotor and fixed-wing types, which can take off and land vertically. The key objective of the present work is to investigate the aerodynamic characteristics of a vertical takeoff and landing (VTOL) fixed-wing Tricopter (VFW tricopter) UAV by creating a 3D model in Plane-Maker and simulating that model to get thrust, lift force, drag force, and static pitch stability. X-Plane 12 was used to design and study the aerodynamic characteristics of a VTOL Tricopter UAV during the hover-forward transition flight phase. It has been found that the value of thrust force was high before transition, which is suitable for vertical takeoff and maneuvering. During the transition, it starts decreasing. After the transition, the thrust goes down and then stabilizes at lower values to sustain forward motion. This thrust reduction enables the plane to glide. In terms of pitch stability, at the beginning of the transition phase, the VFW tricopter UAV was unstable. Afterwards, the pitch stability stabilizes, indicating that the UAV has adjusted to a stable forward flight. Transition thrust vector changes may cause instability at the start of the transition phase. Lift force was high and stable during hover, decreased during transition, and showed fluctuations as the tricopter UAV adjusted to forward flight. Drag force was relatively high during hover and decreased during transition, stabilizing at lower values during forward flight. The frontal area of the tricopter UAV decreased, which caused the plane to produce less drag. This study aids in designing and understanding the aerodynamic characteristics of a VFW tricopter UAV during the hover-forward transition flight phase.